1970
DOI: 10.1111/j.1399-3054.1970.tb06486.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ascorbic Acid, when Applied to the Rooting Medium, on Nodulation and Nitrogen Fixation in Gram (Cicer arietinum)

Abstract: Plants of a pure line variety, G 24, of Cicer arietinum L. were grown in sand culture. After an initial dose of a complete nutrient solution, a nitrogen free nutrient solution was supplied to the sand at intervals and a standard rhizobial culture was added twice. The plants were treated with two concentrations of ascorbic acid (20 mg/l and 100 mg/l) through the rooting medium. At suitable intervals two pots from each treatment were sampled. Observations were made regarding the earliest initiation of nodulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1972
1972
2004
2004

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…A haem-totyrosine cross-link has been observed in Mb treated with H202 [41], and if the radical is indeed situated at tyrosine-132 in the MetLb proteins, a similar event may occur. In this context it would be expected that the above compounds, which react with the phenoxyl radical, might protect against inactivation and degradation; previous reports have shown that ascorbic acid can slow down the destruction of Lbs in root nodules [42] and that salicylate, thiourea or desferal can inhibit haem degradation [40], suggesting that such reactions may be of importance. The radical also appears to undergo further reaction with excess H202, as the intensity of this signal decreases with increasing H202 concentration (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A haem-totyrosine cross-link has been observed in Mb treated with H202 [41], and if the radical is indeed situated at tyrosine-132 in the MetLb proteins, a similar event may occur. In this context it would be expected that the above compounds, which react with the phenoxyl radical, might protect against inactivation and degradation; previous reports have shown that ascorbic acid can slow down the destruction of Lbs in root nodules [42] and that salicylate, thiourea or desferal can inhibit haem degradation [40], suggesting that such reactions may be of importance. The radical also appears to undergo further reaction with excess H202, as the intensity of this signal decreases with increasing H202 concentration (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, while Bashor and Dalton (1999) focused their studies regarding the effects of enhanced ascorbate on protection against oxidative damage showing that lipid peroxides were decreased, these authors noted that ascorbate feeding increased the average number of nodules per plant. Earlier studies had also reported that exogenous ascorbate led to increased nodule numbers as well as earlier nodule initiation and delayed senescence, with resultant large increases in plant yields (Swaraj & Garg, 1970). Furthermore, the inclusion of ascorbate and ascorbate peroxidase in a model system containing Bradyrhizobium japonicum bacteroids and leghemoglobin resulted in large increases in nitrogenase activity and enhanced oxygenation of haem proteins (Ross et al ., 1999).…”
Section: Redox Homeostasis and Programmed Cell Death During The mentioning
confidence: 95%
“…Previous indications of the role for ASC in N # fixation can be found in the largely overlooked work from India, excellently reviewed by Chinoy (1984). These studies, which include notably the experiments of Swaraj & Garg (1970), reported that exogenous application of ASC led to earlier nodule initiation, to delayed senescence and to increases in nodule number, weight and nitrogen content as well as in the overall growth and yield of several leguminous plants. In the most remarkable case, a more than five-fold increase in ' fodder yield ' was observed in response to foliar spraying with ASC.…”
Section: mentioning
confidence: 99%